Community development in rural America: the power to exchange capital resources in Norton County, Kansas. - Monier, Janis Pabst (Kansas State University, 2011)
Although rural communities have great diversity, each rural community has resources that can be invested to develop community capital resources. Every rural community not only has resources that are held by local community members, each rural community is also embedded in a larger social network that has the power to exchange resources for its own benefit. Therefore, the holders of a rural community’s resources also have the power to influence the distribution of these resources. As a way to determine who holds the community’s capital resources and begin the community development process, Flora et al. (2006) encouraged rural community development practitioners to perform an assessment of their community’s built, financial, political, social, human, cultural, and natural capitals. The case study method was utilized for the research conducted in this study because of its ability to aid in determining the success or failure of Norton County Economic Development’s Downtown Program, which focused on the revitalization of Norton County’s downtown areas. It was revealed that many of the Downtown Development programs were successfully implemented because the resources that were controlled by local and outside power structures, which also constituted the dynamic and interactive power structure within that system, were identified, mobilized, and utilized in this rural economic development program. This study contributed to sociological knowledge because it looked at the ability of dynamic and interactive power structures to control capital resources in rural community development. As well, this study extended the literature on the importance of participation, solidarity, and the exchange of resources in rural community development, and added to the research on the use of community capitals in identifying and utilizing capital resources in planning rural community development programs that are successful.
Keywords: Rural community development; Capitals; Resources; Power; Participation; Solidarity; Sociology (0626)